Testing a modified perceived exertion scale for Alzheimer's disease. Issue 1 (30th January 2015) - Yu, Fang; Demorest, Shanda L.; Vock, David M.
Abstract: Standardized methods for prescribing and monitoring exercise intensity are needed to advance exercise research in Alzheimer's disease (AD). The purpose of this study was to evaluate the concurrent validity of a modified 1–10 Rating of Perceived Exertion (RPE) scale against heart rate (HR) in older adults with mild‐to‐moderate AD ( N  = 8, age 77–87 years). RPE and HR were assessed every 5 min during each exercise session with 3, 988 data pairs. Pearson and Spearman correlations and mixed models for correlated data were used for analysis. Results show the correlation between RPE and HR and between RPE and change in HR from resting was −.11 ( SE  = .15) and −.31 ( SE  = .17), respectively. The proportions of variance explained by RPE overall, RPE within participant, and RPE within session were only 4.0, 5.3, and 6.7%, respectively. We conclude that the modified 1–10 RPE scale did not show concurrent validity to HR, with large between‐individual variability.